ChemInform Abstract: Recent Progress in Luminescent Liquid Crystal Materials: Design, Properties and Application for Linearly Polarized Emission. Issue 38 (3rd September 2015) - Wang, Yafei; Shi, Junwei; Chen, Jianhua; Zhu, Weiguo; Baranoff, Etienne
Abstract Review: 121 refs.